Un musulman peut-il vivre sur une terre occupée ? L’avis de Ḥammād b. Muḥammad al-Sūqī, un ʿālim touareg, sur la colonisation française - Lefebvre, Camille (Arabica, 2025)
At the beginning of colonial occupation in the early twentieth century in central Sahara and Sahel, Arabic language and script, widely in use for centuries in these Muslim societies, continued to be the vehicles of law, religion, personal writing and correspondence, including with the colonisers. However, the importance of Muslim writing culture and its role in the early days of colonial occupation are still largely to be assessed. The intellectual responses of Muslim scholars to colonialism in this area reflect the four classical Islamic answers on the matter: avoidance through hiǧra, submission, confrontations especially through ǧihād and alliance or accommodation. This paper analyses and offers a translation of a manuscript composed by a Kel Essuk Tuareg scholar from what is today Mali, who chose to accommodate the colonisers and produced a text in response to the accusations of apostasy (takfīr), perversion (tafsīq) and injustice (taǧwīr), levelled against his community.